YASHIL GOL’S ECO-TOURISM POTENTIAL: STUDY CASE - Mammadova, Ulviyya (Asian Journal of Aquatic Sciences, 2025)
The richest eco-tourism potential and real ecosystem of Yashil Gol were studied using remote sensing methods in aerospace sources. Based on these materials, the eco-geographical factors of the lake were revealed using OpenStreetMap and Google Earth. The lake territory comprises 2,551 m² (0.26 ha), and the total perimeter of the lake circle is 202.4 m. The lake’s absolute height is about 909 m above sea level, and the relative height is 1.37 km. The lake shape resembles an oval leaf from space. Consequently, the map length is 76.60 m, but the ground length is approximately 76.96 m, with a heading of 193.43° on the Google Earth map. The lake’s map width is 63.37 m, but the ground width reaches 63.39 m, with a heading of 90.59 ° on the Google Earth map. Yashil Gol is located at 40°45'35"N latitude and 48°32'19"E longitude. The eco-tourism reserves of Yashil Gol haven't been studied by researchers today. Correspondingly, the climate conditions of the lake territory were investigated, and the data are presented in the paper. According to Landsat and other aerospace materials, as well as visits to the lake throughout the four seasons, monitoring deals with climate, forest, and visitor impacts. The woodland cover square around the lake was defined as about 0.88 ha within a 678 m perimeter. There is only one small café on the lakeshore. None of the cottages, hotels, or hostels are located here. Orthofauna members are observed in Autumn as wild birds migrate to warmer areas. The birds are mainly included in the «Green Book» and «Red Book» of the Republic. To investigate the entire ecosystem of Yashil Gol, researchers from various scientific fields must study it.